The motivational beliefs and attitudes about writing of international students enrolled in online academic English classes during the COVID-19 pandemic - Collins, Penelope; Leo, Michael S.; Eslami, Maryam; Hebert, Michael; Levine, Julian; Lee, Jerry Won (Frontiers in Psychology, 2024)
Despite the growing attention to motivation, less is known about international students' motivational beliefs and attitudes about academic writing. In this study, we aimed to explore the motivational factors influencing international students' performance in academic English classes at a large public research university in the western United States. Specifically, we examined students' self-efficacy, goal orientation, beliefs, and affect for writing, along with their malleability, and their contributions to academic achievement in academic English writing classes. The sample comprised 97 students, predominantly from China, enrolled in online academic English courses. Exploratory factor analysis tended to extract more complex models of the motivational constructs than principal component analysis. Students' self-efficacy and enjoyment of writing significantly increased from the beginning to the end of the 10-week term, suggesting motivational factors' malleability. Hierarchical linear modeling revealed that students' self-efficacy at the beginning of the term positively predicted their final grades.However, logistic mixed modeling revealed that students who held stronger beliefs in writing as a means of exploring and expressing ideas had lower odds of passing. Our findings contribute to the understanding of international students' motivation in academic English settings in higher education and offers potential pedagogical interventions to enhance their academic success.